أحكام الدخانوالمتعلقات به في الفقه الإسلاميالرسالة المقدمةلنيلدرجةماجستير في برنامج الشريعة الإسلاميةقسمالفقهو أصولهبجامعةسو راكرتاالمحمدية(Hukum Rokok dan Yang Berkaitan Dengannya Didalam Fiqh Islam) - Suratno, Suratno; , Dr.Muindinillah Basri, M.A; , Dr.Abdul Kholiq Hasan,M.Ed (2013)
The most population of Muslim countriesin the world and especially in our country, Indonesia, are habitual smoker. It's damage and make the soul, spirit, and body to the causes of death due to smoking. We found differences in provisions on smoking and provisions belongings in Islamic jurisprudence. This requires deep research to this topic especially regarding justice and a binding ruling of religius in the smoke and related what happensin the human society. The type of research that carried out by the researcher of this study is literature research, and to analyze those facts, the researcher took the following approaches are: Descriptive Method, Inductive Method and Analysis Method. By this research the researcher was deduce that the rule of current issues in the community because of the smoke in Islamic jurisprudence such as selling smoke and the cultivation and giving fasting break by smoking, company from dealing with smoker,scholarship from Tobacco Company,Therapeutics smoke and the leadership of smoker is proscribed, by this the researcher was agree by the reason who proscribed it and their evidence.The researcher sure that smoke damage are greater than it's benefit. Whereas acording to the researcher the provisions ofthe problems that was happened in the society as the prohibition of husband on their wife to smoke is the duty, and causing smoke garlic and onions when the researcher is not appropriate. The smoke is harmful to body and mind, health, money and other, and long as the well is absolutely proscribed to drink and chew also the cultivation, manufacture, sale and purchase and also inhalant to nose as it's inhalant snuff.